Penyelesaian Sengketa Tanah Wakaf di Kecamatan Medan Sunggal Ditinjau dari Hukum Islam - Hidayat; Fatimah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Waqf land has many benefits for the community. Unfortunately, many waqf lands are not equipped with waqf deeds. This has the potential to create problems because after the waqif passes away, heirs or family members can reclaim the land. A real example occurs with waqf land that has already been built into a mosque in the Medan Sunggal sub-district, which contradicts the requirements of waqf in Islamic law. This research aims to: (1) identify the conditions and pillars of waqf according to Islamic law, (2) understand the methods of resolving waqf land disputes, and (3) analyze the Islamic legal perspective on waqf land disputes in the Medan Sunggal sub-district. The method used is normative-empirical, referencing various sources such as books, journals, legislation, observations, interviews, and other supporting literature. The results of this study illustrate how disputes over waqf land that already has a mosque can be resolved according to Islamic law.